2020
DOI: 10.4103/jfmpc.jfmpc_588_20
|View full text |Cite
|
Sign up to set email alerts
|

Disability ethics in the coronavirus crisis

Abstract: The disability viewpoint is fundamental for understanding and advancing social justice for everyone in the population. Despite this fact, it is regularly dismissed by public health experts and policymakers. Understanding of disability rights is central in an all-inclusive COVID-19 preparedness. This paper attempts to explore disability ethics in understanding structural discrimination, equitable practices, respect for disability culture and ways to safeguard health care professionals with disabilities in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 18 publications
1
47
0
2
Order By: Relevance
“…People with visual or hearing impairments also may face infection risk because of a lack of accessible information on preventive measures during the initial stages of the pandemic. [ 16 , 48 , 49 , 50 ] In Low- and Middle-Income Countries (LMICs), the situation can be worse [ 49 ]. For instance, an audit of press conferences in LMICs showed that only 65% of countries have used a sign language interpreter, with figures varying from 33% to 88% [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…People with visual or hearing impairments also may face infection risk because of a lack of accessible information on preventive measures during the initial stages of the pandemic. [ 16 , 48 , 49 , 50 ] In Low- and Middle-Income Countries (LMICs), the situation can be worse [ 49 ]. For instance, an audit of press conferences in LMICs showed that only 65% of countries have used a sign language interpreter, with figures varying from 33% to 88% [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other published accounts point out that, in the USA, some states were endorsing guidelines to withhold ventilators and treatment from those with certain neurological impairments and intellectual disabilities [ 53 , 56 , 59 , 62 ]. In some jurisdictions, policies have been issued for people with disabilities to have a lower priority to receive critical and lifesaving medical care; at a very minimum, confusion around this (or lack of clear statements otherwise) could further limit access to lifesaving care for people with disabilities [ 6 , 28 , 44 , 46 , 48 , 53 , 56 ]. For example, guidelines stating that survival of younger healthy persons is to be prioritized relative to “chronically debilitated patients” can be interpreted to disadvantage people with disabilities, even if young or otherwise healthy [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The task relevance of the bioethics and research ethics committees of hospitals as having a substantial role in decision-making was deliberated and reactivated. The position of preserving fundamental rights in a crisis scenario entails critical routes with greater balance, apart from biased and discretional decisions ( 7 ). Certainly, many collaterals have emerged from these curves, and in the case of the guidelines, the challenge is to link them to decision making with a legal basis, beyond the traditional figure of recommendations.…”
mentioning
confidence: 99%